Centaurea achilleifolia (Asteraceae), a new endemic species from the Oriental Middle Atlas of Morocco - Homrani Bakali, A.; Susanna, A. (Phytotaxa, 2022)
Centaurea achilleifolia (C. sect. Melanoloma) is illustrated and described as a new species, with records in the Oriental Middle-Atlas of Morocco (Bou Naceur mountain). It differs from similar taxa in the section by its peculiar bipinnatisect leaves, which recall some Achillea species.